2007
DOI: 10.1130/g23354a.1
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial fossils and microbial dolomite in Triassic stromatolites

Abstract: Triassic stromatolitic dolomite from Italy preserves mineralized bacterial remains, one of the fi rst unequivocal identifi cations of such structures in the geological record. They consist of empty spheroids ~1.0 µm diameter resembling coccoid bacteria, and smaller, 150-400 nm, objects interpreted as dwarf bacterial forms, occurring within and between syn-sedimentary dolomite crystals. Moreover, gently folded sheets, 100-200 nm thick and several micrometers long, form a sub-polygonal network reminiscent of EPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(56 citation statements)
references
References 28 publications
5
51
0
Order By: Relevance
“…The same mode of syn‐sedimentary to early diagenetic alteration of the organic cell walls in microfossils, thought to be formed by less resistant chemical compounds, have been observed in mineralized bacteria preserved in Triassic stromatolites (Perri & Tucker 2007). In the specimens of organic walls of bacteria‐like nannofossils (150–400 nm in diameter), the wall is formed by fabric‐destructive nano‐crystal aggregates of dolomite, appearing in a shape that mimics the ‘stacks of organic compounds’ in cell wall layers of the Cryogenian leiospheres.…”
Section: Cryogenian Microfossils and Their Cell Wall Ultrastructurementioning
confidence: 69%
“…The same mode of syn‐sedimentary to early diagenetic alteration of the organic cell walls in microfossils, thought to be formed by less resistant chemical compounds, have been observed in mineralized bacteria preserved in Triassic stromatolites (Perri & Tucker 2007). In the specimens of organic walls of bacteria‐like nannofossils (150–400 nm in diameter), the wall is formed by fabric‐destructive nano‐crystal aggregates of dolomite, appearing in a shape that mimics the ‘stacks of organic compounds’ in cell wall layers of the Cryogenian leiospheres.…”
Section: Cryogenian Microfossils and Their Cell Wall Ultrastructurementioning
confidence: 69%
“…The past presence of microbial mats is further supported by SEM investigations, which revealed filamentous structures that may be mineralized remains of extracellular polymeric substances (EPS) (Fig. 4c) (Perri and Tucker 2007;Spadafora et al 2010). This peculiar bed in the Kössen Formation is interpreted as …”
Section: Lithostratigraphymentioning
confidence: 76%
“…Recently, Huang et al (2007) have suggested that intense bacterial sulphate reduction had a direct influence on dolomite precipitation in the Feixianguan Formation. Further evidence comes by way of mineralized bacterial remains in the Triassic stromatolites (Perri and Tucker, 2007). Recently, culture experiments with sulphatereducing bacteria grown at 308C in media simulating the chemistry of an anoxic, hypersaline lagoon have demonstrated artificial dolomite precipitation (Warthmann et al, 2000).…”
Section: Discussionmentioning
confidence: 98%